Implementation of Youth for Environment in School Organization (YES-O) in the Secondary Schools and Its Impact on Science Learning Progress - Saldana, Joy B; Domanog, Joseph Vincent T (Studies in Philosophy of Science and Education, 2024)
The deliberate attempt to prevent the environment from being completely destroyed has gained attention. Schools are recognized as a vital platform for implementing environmental education. Accordingly, the Youth for Environmental in School Organization (YES-O) stands out as the only recognized implemented environmental co-curricular organization in basic education. Hence, this study evaluated the implementation of the Youth for Environmental in School Organization (YES-O) programs and its impact to the students’ science learning progress in the secondary schools in Oquendo 3 District, Schools Division of Calbayog City, Philippines. The study revealed that YES-O successfully implemented its mandated programs. These programs included seed banks and nurseries, the collection of seeds and seedlings from native and endemic species, emphasis on tree planting and care, implementation of water conservation initiatives, promotion of power supply programs, organization of clean-up drives, and implementation of ecological solid waste management programs. Similarly, YES-O programs had a high impact on students' science learning progress, particularly in terms of their pro-environmental behavior and science performance. There was a strong positive relationship between the implementation of YES-O programs and its impact on students' science learning progress. The study promoted creativity in environmental education and positioned YES-O as an effective organization that inspired students to become genuine stewards of the environment thereby contributing to a sustainable future.